Penerapan model pembelajaran kooperatif berbasis permainan terhadap hasil belajar keterampilan bermain bola voli - Daviet, Daviet Dwi Saputra; Ahmad Lani; Agusti Mardikaningsih; Hari, Hari Pamungkas; Muhammad Nidomuddin; Ashari Husen (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to determine the effect of the application of a cooperative game-based learning model on the learning outcomes of volleyball playing skills in Dampit State Junior High School students. This study applied experimental method with pretest-posttest group design. The research sample included 60 students from class VIII who were divided into two groups, namely the experimental group and the control group. The experimental group received the intervention of a game-focused cooperative learning model, while the control group underwent learning with conventional methods. The data obtained in this study were taken through testing volleyball playing skills and observation sheets. The results showed that there was a significant difference in learning outcomes of volleyball playing skills between the experimental group and the control group with a Sig. (2-tailed) of 0.00 > 0.05. The maximum value on the pre-test of game-based cooperative learning is 85 on conventional learning 80. The minimum score on the posttest of game-based cooperative learning was 93 and on conventional learning was 82. The average value in game-based cooperative learning pre-test 76.95, posttest 85.70 while in conventional learning pre-test 74.60 and posttest 77.35, from the results of learning improvement it can be concluded that there are differences in the improvement of student learning outcomes better control class than conventional. This shows that the application of a game-focused collaborative learning model is effective in improving the learning outcomes of volleyball playing skills among Dampit State Junior High School students.